Ответ:
Пошаговое объяснение:
cos²(π/2+x)-cos²(2π+x)=√3/2
(cos(π/2+x))²-(cos(2π+x))²=√3/2
(-sinx)²-(cosx)²=√3/2
sin²x-cos²x=√3/2 |×(-1)
cos²x-sin²x=-√3/2
cos(2x)=-√3/2
2x=5π/6+2πn |÷2 x₁= 5π/12+πn
2x=7π/6+2πn |÷2 x₂=7π/12+πn.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
Пошаговое объяснение:
cos²(π/2+x)-cos²(2π+x)=√3/2
(cos(π/2+x))²-(cos(2π+x))²=√3/2
(-sinx)²-(cosx)²=√3/2
sin²x-cos²x=√3/2 |×(-1)
cos²x-sin²x=-√3/2
cos(2x)=-√3/2
2x=5π/6+2πn |÷2 x₁= 5π/12+πn
2x=7π/6+2πn |÷2 x₂=7π/12+πn.